2014
DOI: 10.2319/060513-430.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional alterations in pharyngeal airway and maxillary sinus volumes in Class III maxillary deficiency subjects undergoing orthopedic facemask treatment

Abstract: RME/FM treatment did not affect at all the volume of maxillary sinuses and actually inhibited the normal expected increase of the volume of the pharynx when compared with a control group comprising normal individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 15 publications
3
38
3
Order By: Relevance
“…There continues to be debate in regard to the airways. Some authors found no significant changes in the sagittal dimensions of the oropharynx or the nasopharynx (Baccetti et al, ), whereas others even claim that the expected increase in pharyngeal volume decreases (Pamporakis et al, ). Other authors reported an increase in volume in the nasopharynx (Lee et al, ; Kaygisiz et al, ; Sayinsu et al, ), the upper airways (Oktay & Ulukaya, ), the oropharynx, and the nasopharynx (Auconi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There continues to be debate in regard to the airways. Some authors found no significant changes in the sagittal dimensions of the oropharynx or the nasopharynx (Baccetti et al, ), whereas others even claim that the expected increase in pharyngeal volume decreases (Pamporakis et al, ). Other authors reported an increase in volume in the nasopharynx (Lee et al, ; Kaygisiz et al, ; Sayinsu et al, ), the upper airways (Oktay & Ulukaya, ), the oropharynx, and the nasopharynx (Auconi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent 3D CBCT study compared airway volumes of subjects treated with protraction face mask and untreated controls. 27 They reported no significant change in the oropharynx as a result of face mask treatment. Interestingly, the authors noted that the oropharyngeal volume in the face mask group was smaller than in untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, cephalometric studies have concluded that while maxillary protraction increased the nasopharyngeal airway, it did not significantly affect the oropharynx. 26,27 Mucedero et al 20 compared Class III patients treated with protraction face mask, protraction face mask with rapid palatal expansion, and untreated controls. While there were statistically significant skeletal improvements with the protraction groups compared with the untreated Class III controls, there was no difference in nasopharyngeal and oropharyngeal dimension between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the relationship between extra oral maxillary protraction and pharyngeal size [17][18][19]. However, no research has ever been done to evaluate the relationship between pharyngeal airway space and tongue appliance.…”
Section: Introductionmentioning
confidence: 99%
“…Pharyngeal size is very important for all patients and particularly for the patient with sleep apnea. The size of the nasopharynx may be of particular importance in determining whether the mode of breathing is predominantly nasal or oral.A few studies have investigated the relationship between extra oral maxillary protraction and pharyngeal size [17][18][19]. However, no research has ever been done to evaluate the relationship between pharyngeal airway space and tongue appliance.…”
mentioning
confidence: 99%